The Effect of Nitric Oxide Inhibition in Spinal Cord Injured Humans with and without Preserved Sympathetic Control of the Vasculature - Brown, Rachael; Celermajer, David; Macefield, Vaughan; Sander, Mikael (Frontiers in Neuroscience, 2016)
Systemic pharmacological inhibition of nitric oxide (NO) causes a hypertensive response, which has been attributed both to inhibition of peripheral NO-mediated vasodilatation and to inhibition of central nervous NO-production leading to a later onset sympathetic vasoconstriction. In the present study we aimed to test the importance of these two mechanisms by comparing the time-courses of the hypertensive responses in spinal cord injured (SCI) subjects with varying degrees of loss of sympathetic vascular control depending on level of injury as well as able-bodied controls. We hypothesized that high level SCI with no sympathetic vasoconstrictor control would have an abbreviated time-course of the hypertensive response to the NO-inhibitor L-NAME, because they would lack the late onset sympathetic component to the hypertensive response. NO production was blocked in 12 subjects with SCI and 6 controls by intravenous infusion of L-NAME (1.55-2.7 mg/kg). We measured blood pressure, heart rate and vascular conductance in the carotid, brachial and femoral arteries before, during, and after 1 hour of L-NAME in a 4-hour protocol. Peak increases in mean arterial pressure were significantly larger in high level SCI vs controls: 32 ± 6 vs. 12 ± 2 mmHg (both groups received 1.55 mg/kg). The decreases in vascular conductance in the brachial and femoral vascular beds were also larger in the high level SCI group, whereas decreases in heart rate and carotid conductance were not significantly different between the groups. There were no indications of any abbreviated responses in blood pressure or vascular conductance in the high level SCI compared to control. The mid level and low-level SCI subject had responses similar to controls. These data confirm previous reports that NO inhibition causes a larger increase in blood pressure in high level SCI, and extend these data by providing evidence for differences in vascular conductance in the limbs. The current data do not support an obligatory important role for sympathetic vasoconstriction in maintaining the hypertensive response to L-NAME in humans.